Normalization of muscle tone in children with cerebral palsy in special schools. - Kruglyak M.; Barishok T. (Kharkov National Pedagogical University, 2011)
The features of using exercise to reduce muscle tone in children with cerebral palsy in training at a special school. The study involved children with cerebral palsy 7-10 years. Presents the results of evaluation of motor function and muscle tone. The efficacy of the use of physical rehabilitation for children with cerebral palsy, a positive effect of using special exercise in stretching the muscles with increased tone, improve motor function and normalization of muscle tone.